2012
DOI: 10.1111/j.1365-3083.2012.02717.x
|View full text |Cite
|
Sign up to set email alerts
|

American Tegumentary Leishmaniasis: Cytokines and Nitric Oxide in Active Disease and After Clinical Cure, With or Without Chemotherapy

Abstract: The influence of immune response on the treatment of American tegumentary leishmaniasis is pointed by several authors, and the existence of protective immunity in self‐healed patients (SH) is also suggested. Thus, interferon‐gamma (IFN‐γ), tumour necrosis factor‐alpha (TNF‐α), interleukin (IL‐) 10, IL‐17, IL‐22 and nitric oxide (NO) production was determined in PBMC culture supernatants from patients with active disease (AD) and after therapy, SH patients and healthy subjects, in response to the soluble antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
2
15
0
1
Order By: Relevance
“…Consistent with this, it has been reported that the injection of anti-TNF-α into mice worsened the Leishmania infection [51]. The phenomena described above could perhaps underlie the protective response that normally keeps the Leishmania parasites in check in most infected human beings [52], [53].…”
Section: Discussionsupporting
confidence: 69%
“…Consistent with this, it has been reported that the injection of anti-TNF-α into mice worsened the Leishmania infection [51]. The phenomena described above could perhaps underlie the protective response that normally keeps the Leishmania parasites in check in most infected human beings [52], [53].…”
Section: Discussionsupporting
confidence: 69%
“…Conversely, we found an increase in IL-17 production in patients infected with L. braziliensis , and there was a direct correlation between the magnitude of the cellular infiltrate and IL-17 [16]. Similarly, IL-17 levels were elevated in L. braziliensis infected patients with disease, but not patients who have resolved their infections [68]. Finally, an association with increased IL-17 and neutrophils has been observed in mucosal patients [17].…”
Section: Discussionmentioning
confidence: 48%
“…Bone marrow-derived dendritic cells pre-exposed to salivary gland extracts from the South American Leishmania sand fly vector L. longipalpis exhibited diminished IL-17 expression when secondarily challenged to inflammation 48. Moreover, peripheral blood mononuclear cells from human donors who self-healed from cutaneous disease expressed less IL-17 compared with individuals presenting with active disease after in vitro rechallenge with soluble Leishmania antigens 55. IL-8 and IP-10 (CXCL10) are potent chemotactic agents responsible for recruitment of neutrophils, monocytes, and other immune cell types and have been shown to be responsible for the abrogation of the visceral forms of leishmaniasis 56.…”
Section: Discussionmentioning
confidence: 99%